Advances and current trend of bioactive papers and paper diagnostics for health and biotechnological applications. (March 2022) - Khan, Mohidus Samad; Shadman, Swarit A; Khandaker, Md. Mursalin R
Abstract : The benefits of many breakthroughs in biotechnology, health, and medicine have often been restricted by the high cost and the limited availability of tests and application devices. There is a need for low-cost bioassays for biotechnological applications and health diagnostics. To facilitate quality health care to resource-limited regions, the point-of-care devices needs to be affordable, sensitive, user-friendly, rapid, and robust. Paper is an ideal ingredient to develop disposable bioassay devices. Bioactive papers can be used to develop paper-based analytical devices for clinical diagnosis, assessing organ dysfunction, and detecting infectious diseases and microorganisms. Bioactive papers can also be used as antibacterial papers in healthcare and food packaging. At present the paper diagnostics is a multibillion-dollar market. Considering the product range and applications in health sector the market potential of bioactive papers is very high. Synchronized scientific and industrial research is needed to develop high quality and consistent commercial products from laboratory proof of concept.